(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2021)
Background: Extra-articular proximal and distal metaphyseal fractures of tibia pose a significant challenge to the surgeons. Debate continues regarding choice of fixation devices. Evaluate these fractures fixation with intramedullary expert tibial nail and extramedullary locking plate and screws. Materials and methods: This is a prospective interventional study which had been conducted in the Department of Orthopaedics & Traumatology, Chittagong Medical College Hospital, Chattogram from July, 2018 to June, 2019. Total 60 cases (30 cases in each group) with proximal and distal metaphyseal tibial fractures (AO/OTA 41A2 to A3 and 43A1 to A3) were taken. Functional assessment was done atleast 6th month of surgery using Tegner Lysholm knee scoring scale and Kaikkonen ankle scale. Results: According to assessment scale, excellent outcome was observed in 20 (66.7%) patients, good in 05 (16.7%), fair in 03 (9.9%) and poor in 2 (6.7%) patients in ETN group while in LPS group, 18 (60%) patients were excellent, 05 (16.7%) good, 04 (14.3%) fair and 03 (9.9%) patients were poor. Difference in functional outcome in both the groups was statistically non-significant. Conclusions: There was no significant difference statistically in functional outcome of patients treated with intramedullary and extramedullary fixation method. JCMCTA 2021 ; 32 (1) : 59-64